Tax education as a catalyst for knowledge to improve the quality of life (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
The general purpose of this article was to analyze tax education as a factor in fostering a culture of civic responsibility and promoting knowledge about citizens' rights and responsibilities, in its role as a contributor to improving the population's quality of life. To achieve this objective, documentary research was conducted, applying operational techniques for managing bibliographic sources. It was concluded that tax education should be integrated into educational systems and policies, so that people understand from an early stage of their lives the importance of knowing their tax rights and responsibilities. This will lead to transparency in the investment of tax resources, which should be allocated to cover public needs and therefore, result in a better quality of life.
Keywords: quality of life; education; tax system